The role of carbonic anhydrase 9 in regulating extracellular and intracellular ph in three-dimensional tumor cell growths. - Swietach, P; Patiar, S; Supuran, C; Harris, A; Vaughan-Jones, R (2009)
We have studied the role of carbonic anhydrase 9 (CA9), a cancer-associated extracellular isoform of the enzyme carbonic anhydrase in multicellular spheroid growths (radius of approximately 300 microm) of human colon carcinoma HCT116 cells. Spheroids were transfected with CA9 (or empty vector) and imaged confocally (using fluorescent dyes) for both intracellular pH (pH(i)) and pH in the restricted extracellular spaces (pH(e)). With no CA9 expression, spheroids developed very low pH(i) (approximately 6.3) and reduced pH(e) (approximately 6.9) at their core, associated with a diminishing gradient of acidity extending out to the periphery. With CA9 expression, core intracellular acidity was less prominent (pH(i) = approximately 6.6), whereas extracellular acidity was enhanced (pH(e) = approximately 6.6), so that radial pH(i) gradients were smaller and radial pH(e) gradients were larger. These effects were reversed by eliminating CA9 activity with membrane-impermeant CA inhibitors. The observation that CA9 activity reversibly reduces pH(e) indicates the enzyme is facilitating CO(2) excretion from cells (by converting vented CO(2) to extracellular H(+)), rather than facilitating membrane H(+) transport (such as H(+) associated with metabolically generated lactic acid). This latter process requires titration of exported H(+) ions with extracellular HCO(3)(-), which would reduce rather than increase extracellular acidity. In a multicellular structure, the net effect of CA9 on pH(e) will depend on the cellular CO(2)/lactic acid emission ratio (set by local oxygenation and membrane HCO(3)(-) uptake). Our results suggest that CO(2)-producing tumors may express CA9 to facilitate CO(2) excretion, thus raising pH(i) and reducing pH(e), which promotes tumor proliferation and survival. The results suggest a possible basis for attenuating tumor development through inhibiting CA9 activity.